Histamine release during intestinal ischemia-reperfusion Role of iron ions and hydrogen peroxide - Boros Mihály; Kaszaki József; Nagy Sándor (1991)
Reactive oxygen intermediates (ROI) play a major role in the mucosal damage developing during the reperfusion period following intestinal ischemia. We have shown previously that histamine (H) release is related to the ROI generated by xanthine oxidase during intestinal ischemia-reperfusion. The present study sought to determine the possible chain of events leading to H liberation. The artery supplying a segment of the ileum was occluded for 2 hr in 51 anesthetized dogs, and plasma levels of H were determined radioenzymatically in the venous effluent. Catalase was applied to scavenge hydrogen peroxide; dimethylsulfoxide and mannitol were used as hydroxyl radical scavengers; the role of catalytically active iron was assessed by using desferrioxamine. Pretreatment with either catalase or desferrioxamine, but not with dimethyl sulfoxide or mannitol, was effective in reducing the postocclusive H release. The results provide further in vivo evidence that ROI are causative agents in H liberation during reperfusion of the ischemic gut. Hydrogen peroxide can interact with catalytically active iron and generate highly reactive oxidants, which in turn are responsible for H release. The exact nature of these oxidants is still uncertain.
Keywords: Klinikai orvostan